SOLUTION PROBLEMS OF ISLAMIC ELEMENTARY STUDENTS IN MEMORIZING THE HOLY QURâ€™AN - Mahmudah, Masrurotul; Aziz, Ikhwan; Habibah, Umi; Fauzan, Fauzan; Amrulloh, Hanif (JMIE (Journal of Madrasah Ibtidaiyah Education), 2020)
Various challenges one after another will confront the prospective Hafidz Al Qur'an. Parents expect their children to be able to memorize the Qur'an. The purpose of this study is to find out genuinely about the problems of non-resident Islamic elementary students who attend the Tahfizdul Qur'an program. This study uses descriptive qualitative methods with in-depth analysis while extracting data using data triangulation, namely: interviews, observation, and documentation. From the results of the study, the problems were found that several causes prevented them from memorizing the Qur'an; including learning problems that quickly disappeared; having difficulty in remembering; still unable to be disciplined in following the memorizing Qur'an program; feeling lazy and comfortable; and more time to play gaged than memorizing. The solution given is calling not to leave new memorization for too long; it is a system of rote repeating; may listen to from others; including tapes, recordings, and others;Â  give understanding to children to understand the meaning of memorized material and try to reflect on it.